The lived experience of long-term overland travel - Philippa Thomas; Christian van Nieuwerburgh (Annals of Tourism Research Empirical Insights, 2022)
This study analyses the lived experience of “overlanding”, defined as a form of self-reliant long-term adventure travel by vehicle in which the journey is perceived to be more important than the destination. The study builds on recent research into “lifestyle travel”, “voluntary simplicity” and “transformative tourism”, and travelling cohorts from backpackers to campervan users to ocean-going adventurers. Given the under-researched nature of long-term overlanding as a lifestyle, the methodology used is interpretative phenomenological analysis (IPA), enabling the capture of rich idiographic data from a series of in-depth semi-structured interviews. Four overall themes emerge: the simple life, freedom, development of self, and positive relationships. The five participant couples are in mid-life, also allowing for focus on matters of life-choice and purpose.